Production Dynamics and Factors Affecting Peri-Urban Agriculture - J.Rohit , B.K.Singh , N.V. Kumbhare, S. K.Dubey, (Indian Journal of Extension Education, 2022)
The result of study on rice ( ) production and marketing peri-urban agriculture has assumed vital importance due to ongoing phenomenons of urbanization all around the globe.The studywas undertaken inHapur district of Uttar Pradesh and Faridabad district of Haryana on production dynamics of peri -urban agriculture. One hundred and twenty respondents were selected randomly to obtain significant information. The study revealed that 83.33 per cent periurban farmers were in the category of dynamic with respect to production dynamics index.The 44 per cent of farmers were having high school level education,were dynamic level.Various factors affecting peri urban agriculture were identified in which education, extension contact . showed positive correlationwith production dynamics index.